A thorough clinical study pipeline to discover and validate biomarkers in kidney transplantation: The European BIOMARGIN program - Marquet, Pierre; Humeau, Antoine; Anglicheau, Dany; Naesens, Maarten; Gwinner, Wilfried; Thevenot, Etienne A.; Labriffe, Marc; Essig, Marie (Journal of pharmaceutical and biomedical analysis, 2025)
The European research program BIOMARGIN (Biomarkers of Renal Graft Injuries) seeks to identify and validate non-invasive biomarkers of graft lesions in kidney transplant patients. Graft biopsies represent the gold standard to identify graft lesions, but they are invasive, and their interpretation is subject to large inter-operator variability. Non-invasive biomarkers able to detect graft lesions early would help reduce or eliminate the use of biopsies and propose medical intervention earlier. BIOMARGIN entails a thorough clinical research pipeline for the untargeted discovery, selection and repeated validation of urine, blood and biopsy biomarkers (mRNAs, miRNAs, metabolites, peptides or proteins) of kidney graft rejection or interstitial fibrosis/tubular atrophy. It combines: (i) two case-control studies to identify, confirm and select the best biomarker signatures; (ii) a cross-sectional study to assess their diagnostic performance in a representative population; (iii) a longitudinal cohort study to evaluate their diagnostic and predictive performance in adult and pediatric patients; (iv) very thoroughly standardized and monitored sample collection, preparation, storage and shipment; (v) gold-standard outcomes through centralized, consensus histological assessment of graft biopsies; (vi) untargeted -omics techniques for the discovery, and targeted techniques for the quantitation, of candidate biomarkers; and (vii) a sophisticated statistical pipeline to select biomarker candidates (avoiding confounders), combine them with clinical data and evaluate their diagnostic and prognostic performances. More than 2500 biopsies, 4200 plasma and 9700 urine samples have been collected from > 1300 patients. To the best of our knowledge, there has never been such a comprehensive research program for clinical biomarkers. •BIOMARGIN (Biomarkers of Renal Graft Injuries) is a European research program.•It aims to identify and validate non-invasive biomarkers of kidney graft lesions.•It combines two case-control, a cross-sectional and a longitudinal cohort study.•Sample collection, preparation, storage and shipment conditions are standardized.•It entails a sophisticated statistical /machine learning analysis pipeline.•The outcome is set through centralized characterization of graft biopsies.